A model for evaluating strategic maturity of the local government = Model oceny dojrzałości strategicznej urzędów administracji samorządowej - Szumowski, Witold; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
A significant level of uniqueness and variability of the carried out tasks compel the management of contemporary organizations to continuously search for methods and concepts allowing to increase flexibility in adapting their organizations to ongoing changes. One of such concepts oriented at increasing the levels of flexibility of an organization is strategy, which up to the end of the last century was used mainly in organizations driven by financial results.
Keywords: strategia; dojrzałość strategiczna; urzędy administracji samorządowej; strategy; strategic maturity; local government administration